The power of information: boosting users' chatbot through trust and satisfaction in Indonesian e-commerce - Syafitri, Reren; Alfansi, Lizar (Manajemen dan Bisnis, 2024)
This study aims to investigate the influence of information quality on users' interest in chatbot usage in the context of e-commerce in Indonesia, with trust and customer satisfaction as mediators. The Structural Equation Modeling Partial Least Squares (SEM-PLS) analysis method is used in this research, with data collected from 360 respondents who are e-commerce users in Indonesia. The results of this study indicate that high information quality positively influences users' interest in chatbot usage. Additionally, consumer trust in the chatbot and the level of customer satisfaction also play a mediating role in this relationship. This research provides valuable insights for e-commerce companies in Indonesia to understand the factors influencing customer acceptance of chatbots, emphasizing the importance of ensuring high information quality, consumer trust, and customer satisfaction to enhance the interest in chatbot usage and improve service quality and customer experience.